2023
DOI: 10.3389/fmars.2023.1080386
|View full text |Cite
|
Sign up to set email alerts
|

Submarine canyons as key habitats to preserve Risso’s dolphin (Grampus griseus) populations in the northwestern Mediterranean Sea

Abstract: This paper summarises the occurrence of Risso’s dolphin (Grampus griseus) over 12 years (2009 to 2021) in the northwestern Mediterranean. The study was conducted off the central coast of Catalonia (NE Spain) in an area covering 8,026 km2 and featuring a system of submarine canyons. The habitat is suitable for a wide diversity of species, including deep-diving cetaceans. In addition, a different dataset from other projects was included to compare distances to the coast from different periods. A visual effort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
2
0
0
Order By: Relevance
“…In general, most of the species' suitable habitats were predicted in the Western Mediterranean Subregion, in accordance with most of the known occurrences of the three species in the Mediterranean Sea In particular, the predicted areas for Gg were validated also by the independent dataset in the Western Mediterranean, including the North African coast, where no effort was performed. Indeed, the species is mostly found in the Western Mediterranean Subregion, from the Alborán Sea and the Algerian coast (e.g., Cañadas et al, 2005), to the Spanish continental slope and around the Balearic Islands (e.g., Chicote et al, 2023;Verborgh et al, 2016) and the Provençal Basin (ACCOBAMS, 2021), which confirms the suitability prediction obtained by this study. In the latter area, the species was considered to prefer the upper continental slope (e.g., Bearzi et al, 2011;Praca & Gannier, 2008;Laran et al, 2010Laran et al, , 2017, with a more recent use reported also of offshore areas (e.g., ACCOBAMS, 2021; Azzellino et al, 2016;Labach et al, 2015), in accordance with the prediction of this study.…”
Section: Main Findings On Speciessupporting
confidence: 88%
See 1 more Smart Citation
“…In general, most of the species' suitable habitats were predicted in the Western Mediterranean Subregion, in accordance with most of the known occurrences of the three species in the Mediterranean Sea In particular, the predicted areas for Gg were validated also by the independent dataset in the Western Mediterranean, including the North African coast, where no effort was performed. Indeed, the species is mostly found in the Western Mediterranean Subregion, from the Alborán Sea and the Algerian coast (e.g., Cañadas et al, 2005), to the Spanish continental slope and around the Balearic Islands (e.g., Chicote et al, 2023;Verborgh et al, 2016) and the Provençal Basin (ACCOBAMS, 2021), which confirms the suitability prediction obtained by this study. In the latter area, the species was considered to prefer the upper continental slope (e.g., Bearzi et al, 2011;Praca & Gannier, 2008;Laran et al, 2010Laran et al, , 2017, with a more recent use reported also of offshore areas (e.g., ACCOBAMS, 2021; Azzellino et al, 2016;Labach et al, 2015), in accordance with the prediction of this study.…”
Section: Main Findings On Speciessupporting
confidence: 88%
“…Despite the absence of effort in the Levantine subregion, which prevents reliable conclusions, the predicted suitable areas in the Greek waters (northern Aegean and Corinth Gulf), and along the easternmost coast of the Mediterranean basin seemed likely consistent with the little information available for these areas (e.g., Frantzis et al, 2003;Frantzis & Herzing, 2002;Kerem et al, 2012;Lanfredi et al, 2021;Öztürk et al, 2011;Saad & Mahfoud, 2022). The variables identified by this study as the most relevant for Gg confirm the importance of submarine canyon and depth for the species, which is known to prefer pelagic water with steep shelf slopes and submarine canyons (Azzellino et al, 2008;Azzellino et al, 2016;Cañadas et al, 2005;Chicote et al, 2023;Praca & Gannier, 2008), and highlighted higher Chl-a values among the main drivers shaping the distribution of the species.…”
Section: Main Findings On Speciessupporting
confidence: 71%